The metaverse dilemma : challenges and opportunities for business and society - Krishnan, Chitra; Behl, Abhishek; Dash, Snigdha; Yadav, Prashant Dev (Bingley, U.K. : Emerald Publishing Limited, 2024)
As with any digital technology, there are concerns about how new advancements may affect our health, safety, security, privacy, and economy. The metaverse has potential, but as with any other universe, whether it be physical or digital, it also faces challenges. It is currently undefinable; neither good nor bad can be applied to it, falling under a spectrum that can be either advantageous or harmful to those who engage in it. Focusing on the main issues presented by the metaverse, including implementation, governance, ethical decision-making, sustainability, safety and security, intellectual property, and acceptable behavior issues, The Metaverse Dilemma explores a balanced viewpoint of the metaverse from both a theoretical and practical mindset, examining the challenges and opportunities faced when adopting and implementing the metaverse in business and everyday scenarios. Contributing to the fields of technology and sustainability through the lens of the metaverse, The Metaverse Dilemma is essential reading for entrepreneurs, start-up enthusiasts, students, researchers, and practitioners looking to understand the broader implications of the metaverse on the future of global society.
Part a: Introduction to metaverse -- Chapter 1. Introduction of metaverse in business / Udgam Mishra and Nirma Sadamali Jayawardena -- Chapter 2. The impact of metaverse on businesses / Sridharan. A and Sunita Kumar -- Part b: Technologies driving the metaverse -- Chapter 3. Augmented reality: Shaping the metaverse / Muruganantham Ganesan and B. Dinesh Kumar -- Chapter 4. Artificial intelligence and the metaverse / K K Shihab, Anil Vashisht, Arif Hasan, and Astha Joshi -- Chapter 5. Metaverse and internet of things: A way to smart cities / Anubha Anubha, Govind Nath Srivastava, and Daviender Narang -- Chapter 6. Unleashing digital frontiers: Bridging realities of augmented reality, virtual reality and the metaverse / Arjun J Nair, Sridhar Manohar, Amit Mittal, and Rishi Chaudhry, -- Chapter 7. Non-fungible tokens and blockchain: Foundations for a sustainable metaverse economy / Rim Gafsi -- Part c: How can metaverse contribute to sustainability? -- Chapter 8. Sustainability in the metaverse: Challenges, implications, and potential solutions / Poornima Jirli and Anuja Shukla -- Chapter 9. Metaverse and esg governance: Addressing social and environmental challenges in the virtual world / Supriya Lamba Sahdev, Ahdi Hassan, Chitra Krishnan, Jasmine Mariappan, and Ivan Salazar Chang -- Chapter 10. Metaverse: Transformative pathways for skilling, reskilling, and upskilling in the digital age / Snigdha Dash, Prashant Dev Yadav, Rishi Manrai, and Aditya Kumar Gupta -- Part d: Potential present and future of metaverse technology -- Chapter 11. Metaverse and wellness tourism: An investigation on mixed reality (mr) health care approaches in the tourism industry / Saranya Thaloor -- Chapter 12. Metaverse: A game changer for reshaping fashion industry / Reema Varshney and Nimisha Rana Chaudhary -- Chapter 13. Metaverse in education: Pioneering virtual world for cutting edge hybrid learning experiences / Seema Garg, Namrata Pancholi, Anamica Singh, and Anchal Luthra -- Chapter
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Metaverse; Business & Economics -- E-Commerce -- General; Media studies: internet, digital media and society; E-commerce: business aspects